Systematic Review : Kajian Fitokimia Dan Potensi Farmakologi Jeruk Pamelo (Citrus Maxima) - Mutiah, M.Kes, Roihatul; Qonita, Kesimira; Luthfi, Fitrati Hasanah (Journal of Islamic Medicine, 2023)
Background: The Citrus maxima plant is native to the Malay islands and East India. This plant grows widely in the tropics and has been widely used as medicine. Objectif: The purpose of this study was to study Citrus maxima from the aspect of phytochemical and pharmacological activity. Methods: The method used in this research is PRISMA systematic review. Sources of data obtained from electronic databases PubMed, Science Direct, and Google Scholar. Results: The results of a systematic review showed that the Citrus maxima plant contains naringin, hesperidin, hesperetin, rutin, nobiletin, tangeretin, vitamin C, limonene, lycopene, bergapten, umbelliferone and auraptene compounds. . Conclusion: These compounds have pharmacological activities as antioxidants, anticancer, antibacterial, anti-inflammatory, and antidiabetic